Epidural abscess assessment and management - Ali, Shahnila (International Journal of Research in Medical Sciences, 2017)
Epidural abscess is a medical emergency. Abscesses can expand to compress the brain or spinal cord and cause severe symptoms, perma-nent neurological deficits, or even death. Most spinal epidural abscesses begin as focal pyogenic infection involving the vertebral disc or junction between the disc and the vertebral body and as inflammation pro-gresses, abscess may extend longitudinally in the epidural space, and damage to the spinal cord can happen. Symptoms on presentation may include fever, malaise, back pain, motor weakness, sensory changes, bladder or bowel dysfunction, or paralysis. Most important diagnostic test is MRI because it is positive early in the course of the infection and pro-vides the best visualization of the location and extent of inflammatory changes. MRI with contrast should be performed as soon as possible. Treatment is both medical and surgical. Empirical antibiotic regimen can be vancomycin, metronidazole and third generation cephalosporin or vancomycin and piperacillin-tazobactam among other combinations. Fur-ther guidance by infectious work up. After diagnosis, neurosurgery con-sultation is taken immediately for surgical evaluation and management.